New trauma score versus Kampala Trauma Score II in predicting mortality following road traffic crash: a prospective multi-center cohort study - Damulira, John; Muhumuza, Joshua; Kabuye, Umaru; Ssebaggala, Godfrey; Wilson, Michael; Bärnighausen, Till; Lule, Herman (BMC emergency medicine, 2024)
Mortality due to injuries disproportionately impact low income countries. Knowledge of who is at risk of poor outcomes is critical to guide resource allocation and prioritization of severely injured. Kampala Trauma Score (KTS), developed in 1996 and last modified in 2002 as KTS II, is still widely being used to predict injury outcomes in resource-limited settings with no further revisions in the past two decades, despite ongoing criticism of some of its parameters. The New Trauma Score (NTS), a recent development in 2017, has shown potential in mortality prediction, but a dearth of evidence exist regarding its performance in the African population.
Gesehen am 04.02.2025